English Learning Strategies by the Second Grade Students at a State Junior High School in Kupang, Indonesia (A Case Study) - Norci Beeh; Piter Baun (RIRAI Publisher, 2022)
Learning and mastering English will not be possible if from the beginning we do not have a strong determination. After having a strong determination, all you need to do is find the right English learning strategy. The students used different learning strategies in learning English as a foreign language. This study is designed to find out types of English language learning strategies are used by the students and the factors influencing the choice of learning strategy. On the basis of the nature of the data, a qualitative approach is appropriate to this study. Data were obtained by questionnaire and interview. The result of the analysis revealed that the students used three types of strategies in learning English. The types of strategies are cognitive, metacognitive and social/affective strategies. The more dominant strategy that is used by the students is social/ affective strategy. While the factor influencing their choices of strategies are classified into internal and external factors.